The Linsenmaier Chrysididae collection housed in the Natur-Museum Luzern (Switzerland) and the main results of the related GBIF Hymenoptera Project (Insecta) - Rosa, Paolo; Bernasconi, Marco Valerio; Wyniger, Denise (Zootaxa, 2015)
Historical notes on Walter Linsenmaier, his entomological career and his Chrysididae collection are given. The purpose of this article is to supply the main results obtained during the GBIF digitalization project and the subsequent reorganization of the Chrysididae collection housed in the Natur-Museum Luzern (Switzerland); we also provide the complete list of the 720 taxa described by the Swiss author (species-group and genus-group names). Observations on the type material is given. A new synonymy (valid name is first) is proposed for: C. consanguinea Mocsáry, 1889 = C. consanguinea iberica Linsenmaier, 1959, syn. nov.; C. pyrophana Dahlbom, 1854 = C. pyrophana var. orionea Linsenmaier, 1951, syn. nov.; Hedychridium elegantulum du Buysson, 1887 = H. hybridum Linsenmaier, 1959, syn. nov.; H. perpunctatum Balthasar, 1953 = H. insequosum Linsenmaier, 1959, syn. nov.; Euchroeus (Pseudospinolia) incrassatus (Spinola, 1838) = E. (P.) humboldti jerichoensis Linsenmaier, 1959, syn. nov. A new replacement name Chrysis vulcanica Rosa, nom. nov. is proposed for Chrysis brevicollis Linsenmaier, 1987, nom praeocc., nec Mocsáry, 1899. The lectotype of Chrysis auriceps Linsenmaier, 1959 is designated.